2006
DOI: 10.1159/000099029
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Damage and Malignancy in End-Stage Renal Failure: Do Advanced Glycation End Products Contribute?

Abstract: In end-stage renal disease (ESRD) there is not only excessive morbidity and mortality due to cardiovascular disease but also an enhanced occurrence of various types of cancer. Both are characterized by oxidative stress and inflammation as two of the central underlying causes of the disease states. In cancer, genomic damage has been demonstrated to be of high pathogenetic relevance. DNA lesions may induce mutations of oncogenes and tumor-suppressor genes which, in the long-run, may lead to malignancies if mutag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 141 publications
(100 reference statements)
0
9
0
Order By: Relevance
“…ROS promote formation of AGEs, which cause AGEreceptor-mediated ROS generation with activation of signaling pathways leading to tissue injury and further AGEs accumulation. AGEs have been demonstrated to interact with specific receptors and induce oxidative stress, enhance vascular cell adhesion molecule-1 expression, and increase endothelial adhesiveness for monocytes (Sebeková et al 2007). Our observations demonstrated that AGEs resulted in a significant overproduction of ROS in HUVECs.…”
Section: Discussionmentioning
confidence: 99%
“…ROS promote formation of AGEs, which cause AGEreceptor-mediated ROS generation with activation of signaling pathways leading to tissue injury and further AGEs accumulation. AGEs have been demonstrated to interact with specific receptors and induce oxidative stress, enhance vascular cell adhesion molecule-1 expression, and increase endothelial adhesiveness for monocytes (Sebeková et al 2007). Our observations demonstrated that AGEs resulted in a significant overproduction of ROS in HUVECs.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress and inflammation have been demonstrated to be of high pathogenetic relevance to cancer, especially because of the contribution of genomic damage. Oxidative damage to DNA may cause mutations of oncogenes and tumor-suppressor genes and may represent one mechanism underlying carcinogenesis [119121]. AGEs are thought to be genotoxic.…”
Section: Consequences Of Oxidative Stress and Oxidative Nucleic Acmentioning
confidence: 99%
“…Dialysis treatment, per se , is a potential source of damage and may be responsible for the T-cell specific immunodeficiency correlated with uremia [190]. DNA damage by AGEs may also be important in the development of several forms of cancer, a disease with increased occurrence in CKD patients [191]. …”
Section: Further Aspects Of Immune Dysfunction In Uremiamentioning
confidence: 99%